Language, Art, and the (Social) Body in Modern and Postmodern Aestheticism: A Comparison of Wilde and Nabokov - Kovačević, Predrag S. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
In this paper, the author argues for a theoretical difference between the modern and postmodern aestheticism and considers their political implications arguing that modern aestheticism carried progressive or radical political impulse; whereas, under postmodernism, its character shifted into a reactionary politics. The specific political implications that are derived from these two kinds of aestheticism concern the attitude towards human nature, different kinds of narcissistic tendencies and divergent attitudes towards art/culture. Next, the author uses the examples of Oscar Wilde’s Picture of Dorian Gray and Nabokov’s Lolita to demonstrate how these differences manifest themselves in the works of these two prominent, if not pivotal, artists related to the aesthetic movement in the history of literature. It is concluded that the politics of Oscar Wilde and Vladimir Nabokov differ radically and these differences stem from the fact that their works embody divergent conceptions of aestheticism.